The Enrollment Magnet: How Educational Marketing and Institutional Quality Shape Student Interest in Vocational Schools - Irwan Fathurrochman; Putri Marina; Rediansyah Pratama; M Ramadani; Refal Alamsyah; Khalid Ilias Basheer Qolamani (Universitas Nurul Jadid, 2026)
Increasing competition among educational institutions has encouraged schools to adopt more strategic approaches in communicating the value of their educational services. Educational marketing is no longer limited to promotional activities; it has become an integral part of how schools build credibility and present the relevance of their programs to prospective students and their families. This study examines how educational service marketing strategies are implemented, how school stakeholders contribute to promotional efforts, and what factors influence prospective students’ interest in vocational education. A qualitative research approach was employed using in-depth interviews, documentation, and field observations to capture the perspectives of individuals involved in school marketing and educational management. The findings show that educational marketing is carried out through a combination of direct outreach activities, such as visits to feeder schools and open house events, alongside the use of social media to broaden information dissemination. These efforts are reinforced by the participation of teachers, alumni, and students who contribute to shaping a credible institutional image. In addition, prospective students’ decisions are influenced by several institutional characteristics, including the clarity of vocational programs, affordable tuition fees, accessible location, alumni experiences, and the availability of practical learning facilities. These findings offer practical implications for educational managers in designing marketing strategies that integrate stakeholder involvement with the strengthening of educational services.